Disnep's pocahontas (Grolier Enterprises Danbury, Connecticut, 1995)
*Pocahontas* is also inspired by the historical figure of Pocahontas, a Native American woman known for her connection with the Jamestown settlers. In various retellings, she is depicted as a peacemaker who navigates the complexities of colonialism, cultural identity, and her own agency. The stories often highlight her bravery, compassion, and the impact of her actions on both her tribe and the settlers.